Bistacrine derivatives as new potent antimalarials. Issue 16 (15th August 2016) - Schmidt, Ines; Pradel, Gabriele; Sologub, Ludmilla; Golzmann, Alexandra; Ngwa, Che J.; Kucharski, Anna; Schirmeister, Tanja; Holzgrabe, Ulrike
Graphical abstract: Abstract: Linking two tacrine molecules results in a tremendous increase of activity against Plasmodia in comparison to the monomer. This finding prompted the synthesis of a library of monomeric and dimeric tacrine derivatives in order to derive structure–activity relationships. The most active compounds towards chloroquine sensitive Plasmodium strain 3D7 and chloroquine resistant strain Dd2 show IC50 values in the nanomolar range of concentration, low cytotoxicity and target the cysteine protease falcipain-2, which is essential for parasite growth.